Human rights : questions and answers - Levin, Leah (Leah Sarah); Plantu, 1951-; Unesco Publishing (Paris : UNESCO Pub., 2009)
This book provides information on human rights standards, mechanisms for their promotion and protection, organizations working for human rights, and major international events. It also includes reflections on the main challenges to human rights. This revised edition reflects substantial recent developments in the field of human rights. The publication is one of UNESCO's contributions to the International Year of Human Rights Learning (2009) and the World Program for Human Rights Education, launched in 2005.--Publisher's description.
pt. 1. International human rights law : questions and answers. Human rights : general introduction -- The International Bill of Human Rights -- International instruments concerning specific human rights issues -- International instruments related to the protection of specific groups -- Procedures for the promotion and protection of human rights -- Protection of human rights in times of armed conflict and responses to systematic and gross violations of human rights -- United Nations bodies, programmes and specialized agencies dealing with human rights -- Regional human rights instruments and procedures -- The role of civil society and the private sector in the field of human rights -- Human rights education -- Contemporary challenges -- pt. 2. The Universal Declaration of Human Rights : what each article means.
Includes bibliographical references.
NLJCols20082021
Keywords: Human rights -- Miscellanea; Human rights; Trivia and miscellanea